The Effect of a Learning Partner Model-Based Program on Spreading Cancer Prevention Knowledge Using Community Health Volunteers in Japan - Hiroko Yako-Suketomo; Asae Oura; Kayoko Katayama; Kyohei Saito; Ken Ohashi; Ana M. Navarro (SAGE Publishing, 2022)
Objectives: This study examines the implementation and short-term effects of a Learning Partner Model (LPM)-based educational program on cancer prevention and control information for community health volunteers in Japan. Methods: The program was undertaken by 3 local governments in collaboration with a government initiative and offered a 90-min group workshop to community health volunteers. Community health volunteers (primary participants) recruited in turn friend or family members (secondary participants) with whom they were prepared to share the content of the workshop with the help of printed materials received in the workshop. We conducted self-administered paper and pencil questionnaire surveys before, immediately after, and 3 months after the workshop. The t-test, Fisher's exact test, paired t-test, and McNemar test were used to compare the 2 groups' demographic characteristics and healthy habits at pretest. Repeated measures ANOVA was used to compare cancer prevention knowledge between groups and over time. Results: Of 142 participants, 107 pairs of learning partners (primary and corresponding secondary participant) completed all questionnaires. All primary participants and 37.4% of the secondary participants were women, and 57.9% of the learning partners were spouses. The results showed significantly higher correct answers on the cancer-prevention knowledge questions in the post-workshop and follow-up surveys compared to the pre-workshop survey ( P  < .001). The increase in knowledge was observed in all learning-partner groups in all 3 sites. Conclusion: The study demonstrates a promising strategy that can be adapted to the health needs of the community beyond cancer prevention and control, building on the efforts of local governments and government health initiatives.